Engineering Characterisation of Wearing Course Materials Modified with Waste Plastic - Mashaan, Nuha S (MDPI, 2022)
This review paper shows several sections of bitumen, asphalt mixtures, polymers, and waste plastic in pavement engineering. The paper reviews and evaluates the influence of using waste polymer in improving the rheological and engineering properties of the modified binder and mixtures. Evaluation of properties and design of stone mastic asphalt mixtures are reviewed. Reports and studies had investigated the advantages and importance of using polymer in bitumen modification; however, they yet show a gap in research in terms of the role of waste polymer in improving the durability, aging, and fatigue life in the long term of service.